Does the antimicrobial-impregnated peripherally inserted central catheter decrease the CLABSI rate in neonates? Results from a retrospective cohort study - Bayoumi, Mohammad A. A.; van Rens, Matheus F. P. T.; Chandra, Prem; Masry, Alaa; D’Souza, Sunitha; Khalil, Amr M.; Shadad, Afaf; Alsayigh, Safaa; Masri, Razan M.; Shyam, Sunitha; Alobaidan, Fatima; Elmalik, Einas E. (Frontiers in Pediatrics, 2022)
Abstract: Background: The use of antimicrobial-impregnated Peripherally Inserted Central Catheters (PICCs) has been introduced in the last few years to neonatal units aiming to reduce the Central Line-Associated Blood Stream Infection (CLABSI). Methods: This retrospective observational study aimed to compare the CLABSI rates and other catheter-related parameters including the insertion success rates and catheter-related complications in the antimicrobial-impregnated and conventional (ordinary) PICCs in NICU between 2017 and 2020. Results: Our dedicated PICC team including physicians and nurses inserted 1242 conventional and 791 antimicrobial-impregnated PICCs over the study period from 2017 to 2020. The mean ± SD for the birth weight in all babies who had a PICC line was 1343.3 ± 686.75 gm while the mean ± SD for the gestational age was 29.6 ± 4.03 weeks. The overall success rate of the PICC insertion is 1815/2033 (89.3%) while the first attempt success rate is 1290/2033 (63.5%). The mean gestational age, birth weight, age at catheter insertion and catheter dwell time was 28.8 ± 3.24 weeks, 1192.1 ± 410.3 gm, 6.3 ± 10.85 days, and 17.73 ± 17.532 days in the antimicrobial-impregnated catheter compared to 30.1 ± 4.39 weeks (P< 0.001), 1439.5 ± 800.8 gm (P< 0.001), 11.1 ± 25.9 days (P< 0.001), and 14.30 ± 10.964 (P< 0.001) days respectively in the conventional PICCs. The use of the antimicrobial-impregnated catheter was not associated with any significant reduction in the CLABSI rate (per 1000 days dwell time), either the overall [P = 0.11, Risk Ratio (RR) (95% CI): 0.60 (0.32, 1.13)] or the yearly CLABSI rates. Conclusions: The use of miconazole and rifampicin-impregnated PICCs did not show any significant reduction in the CLABSI rate in neonates compared to the conventional PICCs. However, it has a higher overall rate of elective removal after completion of therapy and less extravasation/infiltration, occlusion, and phlebitis compared to the conventional PICCs. Further large RCTs are recommended to enrich the current paucity of evidence. Neonatal PICCs impregnation by other antimicrobials is a recommendation for vascular access device manufacturers.